Resepsi Masyarakat Terpencil Terhadap Hadis Dalam Naskah Khutbah Naga di Lilinta, Papua Barat - Al Abza, M. Thohar; Zulfadli, Zulfadli; Hasbillah, Ahmad 'Ubaydi; Syibromalisi, Arif; Karimullah, Suud Sarim (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2024)
This study seeks to explore the pattern of hadith reception in the da’wah practices within the Muslim community of Lilinta, Raja Ampat. In particular, it aims to explore how the hadith text, articulated in Arabic, continues to influence local behaviors, beliefs and customs, despite the community’s lack of cognitive understanding of the language. Employing the living hadith approach and adopting Stuart Hall’s reception theory, this study reveals that Lilinta community demonstrates a habitus pattern of ‘negotiation’ in hadith reception. This study found that while on the one hand the redaction of the hadith was not literally understood by the local Muslims, but the essence of hadith was practiced as cultural doctrines. The pattern of hadith transformation suggests that the hadith and its practices co-exist on divergent paths. Practice transpires through doctrinal channels, while the narrative remains misunderstood. This communal-practical living hadith, grounded in habitus rather than cognition, culminates in robust, albeit static traditions. This study concludes that hadith effectively molds the behavior and beliefs of the Lilinta community when viewed from the practiced behaviors over cognitive understanding.